Pengaruh Waktu Berkualitas Keluarga Terhadap Kesehatan Mental Anak Usia Sekolah Dasar: Penelitian - Deklay Nainggolan; Fadillah Meamogu; Muzaina A. Datunsolang; Nayla Eren Mamonto (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to examine the effect of quality family time on the mental health of elementary school children. Mental health issues in children continue to increase, with family factors playing a crucial role in children's psychological development. This research uses a quantitative approach with a correlational survey method involving 150 elementary school students aged 8-12 years in Surabaya. Data collection was conducted using the Family Quality Time Scale and the Child Mental Health Questionnaire (SDQ). Data analysis used Pearson correlation and multiple linear regression. The results showed a significant positive relationship between quality family time and children's mental health. Families that spend more quality time together, such as eating together, playing, and communicating, have children with better mental health indicators. The contribution of quality family time to children's mental health was 50.7%. This study concludes that quality family time is an important protective factor for children's mental health and recommends that parents prioritize quality interaction time with their children.